2010
DOI: 10.1037/a0020381
|View full text |Cite
|
Sign up to set email alerts
|

Children's conscience during toddler and preschool years, moral self, and a competent, adaptive developmental trajectory.

Abstract: We investigated whether children’s robust conscience, formed during early family socialization, promotes their future adaptive and competent functioning in expanded ecologies. We assessed two dimensions of conscience in young children (N = 100) at 25, 38, and 52 months in scripted laboratory contexts: internalization of their mothers’ and fathers’ rules, observed when the child was alone, and empathic concern toward each parent, observed in simulated distress paradigms. We also assessed the child’s self-percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 72 publications
8
111
0
2
Order By: Relevance
“…In line with previous research on the relationship between negative parenting and ODD [43], the results of the present study suggest that poor monitoring at a very early age predicts increases in temper tantrums, defiant behavior, refusals to comply with authority, and an inability to auto-regulate emotion. As described in Kochanska et al (2010), the parent-child relationship in the preschool period is crucial to consciousness development in children, since this is when parents establish behavioral models and rules that children internalize with time. Children of poor-monitoring parents may fail to associate reward and punishment with their actions, and the absence of constructive parental feedback allows for aggressive and defiant behaviors to proliferate unchecked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with previous research on the relationship between negative parenting and ODD [43], the results of the present study suggest that poor monitoring at a very early age predicts increases in temper tantrums, defiant behavior, refusals to comply with authority, and an inability to auto-regulate emotion. As described in Kochanska et al (2010), the parent-child relationship in the preschool period is crucial to consciousness development in children, since this is when parents establish behavioral models and rules that children internalize with time. Children of poor-monitoring parents may fail to associate reward and punishment with their actions, and the absence of constructive parental feedback allows for aggressive and defiant behaviors to proliferate unchecked.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine reciprocal relationships between parenting practices, CU traits and ODD in a large and representative sample of preschoolers, suggesting a greater ability to generalize results to the preschool population than would be possible with previous high-risk samples [19,9]. A longitudinal design was employed, taking repeated measures of CU traits, ODD and parenting over a period of 3 years from ages 3 to 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not preclude that less demanding forms of morality-self integration occur in childhood [cf. Kochanska, Koenig, Barry, Sanghang, & Yoon, 2010;Krettenauer, 2014;Krettenauer, Campbell, & Hertz, 2013]. Second, self and morality become increasingly integrated in adolescence or emerging adulthood, giving rise to a moral identity.…”
Section: Timingmentioning
confidence: 99%
“…Children with a strong history of committed compliance to parents are likely to see themselves as embracing parents' values and, on this basis, construct a moral self that regulates future behavior [Kochanska, 2002b]. Indeed, in one study Kochanska, Koenig, Barry, Kim, and Yoon [2010] showed that toddlers with a strong history of internalized "out-of-sight" compliance (at 25-52 months) were competent, engaged, and prosocial at 80 months of age. But this effect was mediated at 67 months by the moral self.…”
mentioning
confidence: 99%